2019
DOI: 10.1186/s12889-019-7637-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the village health center project on contraceptive behaviors in rural Jordan: a quasi-experimental difference-in-differences analysis

Abstract: BackgroundAppropriate contraceptive use remains a major health challenge in rural Jordan. The Japan International Cooperation Agency implemented a project aimed at enhancing the capacity of village health centers (VHCs) to improve the quality and quantity of family planning (FP) services in rural Jordan in 2016–2018. Facility- and community-based approaches were integrated into the interventions. We evaluated the project’s impacts on contraceptive behaviors and the effectiveness of the two approaches.MethodsWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Before the project, most VHCs could not provide family planning services. The details of the project design can be found in our study published elsewhere [12]. The study team selected Irbid Governorate as the study site because no similar assistance from other donors had been implemented there before this project.…”
Section: Study Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…Before the project, most VHCs could not provide family planning services. The details of the project design can be found in our study published elsewhere [12]. The study team selected Irbid Governorate as the study site because no similar assistance from other donors had been implemented there before this project.…”
Section: Study Settingmentioning
confidence: 99%
“…The second stage involved selecting households by systematic random sampling in each village, using the household frame of the 2015 Jordan Census which was the same as the methodology used in the JPFHS 2012 [8]. The sampling allocation is shown in S1 Table of the Supporting information, and more detailed sampling procedures can be found in our previous study [12]. When a household did not contain a woman eligible for participation, the household was replaced by the nearest one.…”
Section: Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there was no specific indicator measuring the adolescent group in this study those adolescents who benefitted did in effect trickle their knowledge to their own families and to others within the community. Other studies also showed this pattern in spreading health related information and awareness through adolescent awareness and participation [25], [26].…”
Section: Discussionmentioning
confidence: 66%